Sex and the citizen : interrogating the Caribbean - Smith, Faith, 1964- (New World studies., 2011)
Sex and the Citizen is a multidisciplinary collection of essays that draws on current anxieties about "legitimate" sexual identities and practices across the Caribbean to explore both the impact of globalization and the legacy of the region's history of sexual exploitation during colonialism, slavery, and indentureship. Speaking from within but also challenging the assumptions of feminism, literary and cultural studies, and queer studies, this volume questions prevailing oppositions between the backward, homophobic nation-state and the laid-back, service-with-a-smile paradise or between giving in ignominiously to the autocratic demands of the global north and equating postcolonial sovereignty with a "wholesome" heterosexual citizenry. The contributors use parliamentary legislation, novels, film, and other texts to examine Martinique's relationship to France; the diasporic relationships between the Dominican Republic and New York City, between India and Trinidad, and between Mexico's capital city and its Caribbean coast; "Indigenous" names for sexual practices and desires in Suriname and the Eastern Caribbean; and other topics. This volume will appeal to readers interested in how sex has become an important register for considerations of citizenship, personal and political autonomy, and identity in the Caribbean and the global south. Contributors: Vanessa Agard-Jones * Odile Cazenave * Michelle Cliff * Susan Dayal * Alison Donnell * Donette Francis * Carmen Gillespie* Rosamond S. King * Antonia MacDonald-Smythe * Tejaswini Niranjana * Evelyn O'Callaghan * Tracy Robinson * Patricia Saunders * Yasmin Tambiah * Omise'eke Natasha Tinsley * Rinaldo Walcott * M.S. Worrell